Physiotherapy of patients with CNS damage as a result of a brain tumor - Filarecka, Agnieszka; Biernacki, Maciej; Jęchorek, Michał; Leksowski, Łukasz (Journal of Education, Health and Sport, 2021)
Rehabilitation as a process of return to fitness should take place at every stage of the disease. Stimulation to restore lost motor function should take place all day, including when lying in bed or transferring from one position to another. Placement items are an indispensable component of restoring floatation, as well as the element of nursing the patient. By correct arrangement of the patient we affect the stimulatory nervous system. Thanks to the correct arrangement we prevent bone-joint changes, lymphedema and also stimulate the cerebral cortex. This articule aims to propose the positioning of the patient and his transfers as a passive way of rehabilitation.